2020
DOI: 10.1088/2053-1591/ab61b5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic augmentation of polypropylene composites by hybrid morphology polyaniline particles for antistatic packaging applications

Abstract: In current study polyaniline filled polypropylene (PP/PAni) conductive composites were prepared by a novel premixing technique followed by melt mixing. The PP/PAni composites were also compatibilized by addition of polypropylene grafted maleic anhydride. Polyaniline was prepared by using ammonium per sulphate and ferric chloride as single oxidants. Effects of oxidizing agents (of polyaniline) on composites were studied by morphological, electrical and mechanical properties on composites. FTIR analysis was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is undeniable that by increasing the amount of PANi, a higher improvement in PMMA/PANi composites' conductivity is achieved [164][165][166][167]. However, many researchers agreed that the excess amount of PANi loading leads to the reduction of conductivity in the composite prepared [168][169][170]. Research done by Moussa et al (2017) reported that the direct current (DC) conductivity increased by about two orders of magnitude by increasing the PANi loading from 10% to the saturation loading of 70%.…”
Section: Pani/pmma Ratiomentioning
confidence: 99%
“…It is undeniable that by increasing the amount of PANi, a higher improvement in PMMA/PANi composites' conductivity is achieved [164][165][166][167]. However, many researchers agreed that the excess amount of PANi loading leads to the reduction of conductivity in the composite prepared [168][169][170]. Research done by Moussa et al (2017) reported that the direct current (DC) conductivity increased by about two orders of magnitude by increasing the PANi loading from 10% to the saturation loading of 70%.…”
Section: Pani/pmma Ratiomentioning
confidence: 99%
“…To achieve light weight and good processability, the usually selected polymer matrices for antistatic packaging are polypropylene (PP) 10 and low density polyethylene (LDPE), 11,12 but they are generally electrical insulation 13 . So, polymer matrix with certain antistatic property and environmentally friendly will be appreciated.…”
Section: Introductionmentioning
confidence: 99%